Evidence for brain morphometric changes during the migraine cycle: A magnetic resonance-based morphometry study. (August 2015) - Coppola, Gianluca; Di Renzo, Antonio; Tinelli, Emanuele; Iacovelli, Elisa; Lepre, Chiara; Di Lorenzo, Cherubino; Di Lorenzo, Giorgio; Di Lenola, Davide; Parisi, Vincenzo; Serrao, Mariano; Pauri, Flavia; Fiermonte, Giancarlo; et al.
Neurophysiological investigations have demonstrated that there are unique fluctuations in the migraine brain functional activity between the ictal and interictal periods. Here we investigated the possibility that there are fluctuations over time also in whole brain morphometry of patients affected by episodic migraine without aura (MO). Twenty-four patients with untreated MO underwent 3T MRI scans during ( n  = 10) or between attacks ( n  = 14) and were compared to a group of 15 healthy volunteers (HVs). We then performed voxel-based-morphometry (VBM) analysis of structural T1-weighted MRI scans to determine if changes in brain structure were observed over the course of the migraine cycle. Interictally, MO patients had a significantly lower gray matter (GM) density within the right inferior parietal lobule, right temporal inferior gyrus, right superior temporal gyrus, and left temporal pole than did HVs. Ictally, GM density increased within the left temporal pole, bilateral insula, and right lenticular nuclei, but no areas exhibited decreased GM density. These morphometric GM changes between ictal and interictal phases suggest that abnormal structural plasticity may be an important mechanism of migraine pathology. Given the functional neuroanatomy of these areas, our findings suggest that migraine is a condition associated with global dysfunction of multisensory integration and memory processing.